2021
DOI: 10.2174/0929867327666201111140825
|View full text |Cite
|
Sign up to set email alerts
|

Polyisoprenylated Cysteinyl Amide Inhibitors: A Novel Approach to Controlling Cancers with Hyperactive Growth Signaling

Abstract: : Aberrant activation of monomeric G-protein signaling pathways drives some of the most aggressive cancers. Suppressing these hyperactivities has been the focus of efforts to obtain targeted therapies. Polyisoprenylated methylated protein methyl esterase (PMPMEase) is overexpressed in various cancers. Its inhibition induces the death of cancer cells that harbor the constitutively active K-Ras proteins. Furthermore, the viability of cancer cells driven by factors upstream of KRas, such as overexpressed growth f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…Previous studies on the PCAIs revealed their effectiveness against such cancer phenomena as cell viability, angiogenesis, cell migration and invasion, and cytoskeletal organization [ 19 , 20 , 21 , 23 , 24 , 25 , 26 ]. The present study reports on the synthetic optimization for increased potency and bioavailability as well as the determination of the anticancer molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the PCAIs revealed their effectiveness against such cancer phenomena as cell viability, angiogenesis, cell migration and invasion, and cytoskeletal organization [ 19 , 20 , 21 , 23 , 24 , 25 , 26 ]. The present study reports on the synthetic optimization for increased potency and bioavailability as well as the determination of the anticancer molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%